Hubungan Penggunaan Media Sosial Promosi Kesehatan Sebagai Sarana Holistik terhadap Pengetahuan dan Perilaku Kesehatan Reproduksi Remaja - Anugrah Wulandari; Widya Mariyana; Ellyzabeth Sukmawati (Pusat Riset dan Inovasi Nasional, 2025)
Social media has become an integral part of adolescents' lives, offering quick access to information, including reproductive health information. However, exposure to inaccurate information can pose risks. This study aims to analyze the relationship between social media use and adolescent reproductive health knowledge and behavior. A quantitative research method with a cross-sectional approach and chi-square test was used to examine the relationship between the independent variable (social media use) and the dependent variable (reproductive health knowledge and behavior). The study population was all 10th grade students (23 students) and 11th grade students (30 students) at SMK Tamansiswa Boja Kendal. A sample of 53 respondents was taken using an accidental sampling technique, consisting of students who happened to be present and willing to participate during the study. The results showed that the majority of respondents (56.6%) had low social media usage intensity. The majority of respondents also had a high level of knowledge (75.5%) about reproductive health, with an average score of 8.13 and a median of 10. Most respondents (66.0%) demonstrated positive reproductive health behavior. However, the chi-square test results showed no significant relationship between social media use and levels of knowledge (p = 0.673) or reproductive health behavior (p = 0.495). Although social media did not show a significant direct relationship to adolescent reproductive health knowledge and behavior in the context of this study, the high levels of knowledge and positive behaviors found indicate that existing educational programs, both in schools and from other sources, have been effective. Further research with larger samples and wider geographic variation is needed to understand other factors that influence adolescent health behavior.